When to perform a kidney biopsy in a diabetic patient?. A case report in high altitude city - Vizcarra-Vizcarra, Cristhian (2023)
We report the case of a 54-year-old male patient, high altitude city dweller, with a history of type 2 diabetes mellitus and arterial hypertension in treatment, with persistent microscopic hematuria, creatinine elevation, presence of proteinuria and absence of diabetic retinopathy, who underwent renal biopsy for suspected associated non-diabetic glomerulopathy. Kidney biopsy confirmed the histopathological diagnosis of diabetic nodular glomerulosclerosis Because renal biopsy is usually not performed in diabetic patients, this case is presented and its indications are reviewed. Also, we propose that high altitude could influence in the renal function impairment.